Foot of Carrall: The Historical Maritime Gateway of Gastown - Williams , Trevor (The Northern Mariner / Le marin du nord, 2022)
The arrival of the Canadian Pacific Railway in Coal Harbour in 1887 challenged the traditional public water access to the Burrard Inlet, as the street-end location at the foot of Carrall Street was the longstanding water access to the preceding community of Gastown. Vancouver City Wharf, the would-be public dock, shared this favoured location with boatbuilder Andrew Linton. City Wharf was sold to Union Steamships in 1889, which was a company that understood the meaning of being at this critical historical node. This article explores the history of this maritime gateway, explaining how the company heritage of Union Steamships is conjoined with that of Gastown at the foot of Carrall. L’arrivée de la Compagnie de chemin de fer du Canadien Pacifique en 1887 a remis en question l’accès public traditionnel à la baie Burrard, étant donné que l’emplacement de Coal Harbour au pied de la rue Carrall avait servi pendant longtemps d’accès à l’eau pour la communauté de Gastown. Le quai de Vancouver, l’éventuel quai public, partageait cet emplacement privilégié avec le constructeur d’embarcations Andrew Linton. En 1889, le quai de Vancouver a été vendu à l’entreprise Union Steamships, qui comprenait bien l’importance d’occuper ce lieu historiquement dominant. Le présent article étudie l’histoire de cette porte d’entrée maritime et explique comment l’héritage de l’entreprise Union Steamships est lié à celui de Gastown au pied de la rue Carrall.